Selection Criteria for Radionuclide of Interest in Neutron Activation Analysis - Wasim, M. (The Nucleus, 2021)
This paper describes general selection criteria for suitable activation products to get maximum signal to noise ratio in minimum time. The detection sensitivities for 71 elements which exist in nature, with respect to neutron activation analysis, have been calculated and presented. The paper defines the sensitivity as log (peak area/weight) produced for different radionuclides suitable for activation analysis using five sets of experimental conditions. Although, the current sensitivity factors have been calculated for miniature neutron source reactor (MNSR) having thermal neutron flux of 1012 cm-2 s-1; however, the general pattern of elemental sensitivities will not be affected drastically by changing reactor type. Normalized peak areas have also been presented for the identification of suitable activation products. These normalized areas are independent of experimental conditions used and are therefore general in nature. Finally, real data have been presented from our previous studies, which confirm present findings and provide actual irradiation times along with useful gamma-rays used in the analysis.